Collectively achieving primary health care and educational goals through school-based platforms: financing solutions for intersectoral collaboration - Schiff, Mackenzie; Jha, Ayan; Walker, Dawne; Gonzalez-Pier, Eduardo (Frontiers in Public Health, 2023)
Despite abundant evidence demonstrating that improvements to health and education are positively correlated, and the importance of school-based platforms to achieve shared impacts, collaboration between ministries of health and education remains limited across low- and middle-income countries. Enhancing this collaboration is essential to realize mutually beneficial results, especially following the COVID-19 pandemic, which severely impacted health and education outcomes globally and highlighted the importance of resilient, domestically funded systems for delivering key social services including primary health care and education. We argue that the lack of an effective joint financing mechanism has hindered adoption of collaborative multisectoral approaches such as the WHO/UNESCO’s Health Promoting Schools (HPS) model. HPS is well-positioned to organize, finance, and deliver primary health care and education services through a school-based platform and strategy. Case studies from several low- and middle-income countries highlight the need to expand limited inter-ministerial collaborations to achieve cross-sectoral benefits and ensure sustainability of HPS beyond the lifecycle of external partners’ support. It is important to identify ways to widen the resource envelope for sector-specific activities and create efficiencies through mutually beneficial outcomes. This paper offers two pragmatic solutions: an inter-ministerial joint financing mechanism that starts with alignment of budgets but matures into a formal system for pooling funds, or a fixed-term co-financing mechanism that uses donor contributions to catalyze inter-ministerial collaborations. Achieving sustainability in these initiatives would require engaging the ministries of health, education, and finance; developing a common administrative, financial, and monitoring mechanism; and securing long-term commitment from all concerned stakeholders.